Measurement of cervical grainy sandy patches, homogeneous yellow sandy patches, and abnormal blood vessels proportions in women with female genital schistosomiasis - a clinical validation study of a digital gridded imaging technique - Dragsbæk, Sofie J.; Carstens, Sofie K.; Savkov, Ida; Jøker, Karoline; Randrianasolo, Bodo S.; Leutscher, Peter D.; Arenholt, Louise (Frontiers in Tropical Diseases, 2024)
BackgroundFemale genital schistosomiasis (FGS) is characterised by cervico-vaginal lesions such as grainy sandy patches, homogeneous yellow sandy patches, and abnormal blood vessels. Diagnosis, treatment, and surveillance of FGS presents challenges due to the absence of diagnostic tools in endemic areas. Likewise, a tool for quantification of the lesions is missing. This study aimed to validate the digital gridded imaging technique (DGIT) for quantification of three specific cervical lesion types associated with FGS.MethodsUsing the QubiFier software program, 70 cervical photographic images obtained from women diagnosed with FGS and treated with Praziquantel (PZQ) were randomly sampled for a validation study. The women lived in a S. haematobium-endemic area of Madagascar. For each image, a semi-transparent grid was applied, composed of 424 equally sized squares positioned to cover the cervix. Squares exhibiting any of the specific lesions were marked by three observers to determine the grainy sandy patches proportion (GSP), homogeneous yellow sandy patches proportion (HSP), and abnormal blood vessel proportion (BVP). To train the observers, a set of ten images was utilized, leaving 60 images for the validation. To test inter-rater reliability, the 60 cervical images were scored independently by three observers. To test intra-rater reliability, ten images were scored twice with a two-week interval. Intraclass correlation coefficient (ICC) was used as the main statistical method to assess the reliability between observers.ResultsThe median age of the included women was 26.5 (IQR 20.8-33.0) years, and 74% of them had detectable S. haematobium eggs in their urine. The three proportions were found to be consistent and reliable across the observers, as well as the rescoring on Days 0 and 14. Inter-rater reliability was good for all three cervical lesion types (ICC 0.768-0.890). Intra-rater reliability was good for GSP (ICC 0.832) and excellent for HSP and BVP (ICC 0.932 and 0.982, respectively).ConclusionIn this study DGIT was validated as a potential morbidity detection method for quantification of the three lesion types associated with FGS.